Quantitative Alternations in Word-Formation - Akelaitienė, Gražina (Kalbotyra, 1995)
The article deals with non-automatic quantitative vowel changes which take place in word-formation. They are implicated by a derivational formant. In Lithuanian word formation the vowel quantity typically changes in the direction of increasing duration and intensity (V → V̄) and not the reverse. The functioning morphemes in word-formation are , , as well as , , the latter being less frequent. The long alternant has an informative function: it correlates with corresponding formants and derivational meanings. Quantitative alternations are especially regular in the derivatives of inflection -is, which have the meaning of substantivized actions, e.g., mū̃šis, stȳgis, bū̃vis. The quantity of root vowel can sometimes fulfill an iconic function. In some derivational oppositions, vowel lengthening ar shortening has a direct reference to the verb semantics (it symbolizes more/less intensive and long action) e.g., kìšti → kýšoti, trȳpti → tripinė́ti. Such alternation takes place in derivatives with modifying meanings.